Atypical antipsychotics alter cholesterol and fatty acid metabolism in vitro[S] - Alberto Canfrán-Duque; María E. Casado; Óscar Pastor; Jana Sánchez-Wandelmer; Gema de la Peña; Milagros Lerma; Paloma Mariscal; Franz Bracher; Miguel A. Lasunción; Rebeca Busto (Journal of Lipid Research, 2013)
Haloperidol, a typical antipsychotic, has been shown to inhibit cholesterol biosynthesis by affecting Δ7-reductase, Δ8,7-isomerase, and Δ14-reductase activities, which results in the accumulation of different sterol intermediates. In the present work, we investigated the effects of atypical or second-generation antipsychotics (SGA), such as clozapine, risperidone, and ziprasidone, on intracellular lipid metabolism in different cell lines. All the SGAs tested inhibited cholesterol biosynthesis. Ziprasidone and risperidone had the same targets as haloperidol at inhibiting cholesterol biosynthesis, although with different relative activities (ziprasidone > haloperidol > risperidone). In contrast, clozapine mainly affected Δ24-reductase and Δ8,7-isomerase activities. These amphiphilic drugs also interfered with the LDL-derived cholesterol egress from the endosome/lysosome compartment, thus further reducing the cholesterol content in the endoplasmic reticulum. This triggered a homeostatic response with the stimulation of sterol regulatory element-binding protein (SREBP)-regulated gene expression. Treatment with SGAs also increased the synthesis of complex lipids (phospholipids and triacylglycerides). Once the antipsychotics were removed from the medium, a rebound in the cholesterol biosynthesis rate was detected, and the complex-lipid synthesis further increased. In this condition, apolipoprotein B secretion was also stimulated as demonstrated in HepG2 cells. These effects of SGAs on lipid homeostasis may be relevant in the metabolic side effects of antipsychotics, especially hypertriglyceridemia.